2015
DOI: 10.1111/1440-1681.12337
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel decreases cilia beat frequency of human fallopian tubes and rat oviducts without changing morphological structure

Abstract: SUMMARYLevonorgestrel, a derivative of progesterone, effectively protects women against unwanted pregnancy as an emergency contraceptive. Previous studies have not been successful in determining the mechanism by which levonorgestrel acts. In the present study we analysed cilia beat action and cilia morphology following levonorgestrel exposure in vitro and in vivo using both light and electron microscopy. There was a significant decrease in the ciliary beat frequency (CBF) of human fallopian tubes between mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…; Zhao et al . ), which correlates with the timing of exposure to a chronic hypoxic environment in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…; Zhao et al . ), which correlates with the timing of exposure to a chronic hypoxic environment in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…; Zhao et al . ). Both of these processes are dependent on normal mitochondrial function and ATP production (Dirksen & Zeira, ; Lydrup & Hellstrand, ), particularly in the ciliated cells of the oviduct epithelium.…”
Section: Discussionmentioning
confidence: 97%
“…39,40 Our previous study established that a high dose of LNG could reduce the tubal cilia activity both in vitro and in vivo. 41 To the best of our knowledge, LNG can also reduce muscular contractility in fallopian tubes. 42 A decline of cilia beats and/or muscular contractility can cause the retention of embryotubal transplantation, which has been considered to be mainly responsible for the etiology of TP.…”
Section: Discussionmentioning
confidence: 96%
“…Since LNG‐only pills for emergency contraception are available in an over‐the‐counter form in many countries with a high efficacy in protecting unwanted pregnancy, the problems including ectopic pregnancy following its subsequent contraceptive failure have been confirmed. Compared with the steroid contraception used decades ago, LNG showed a high affinity to its receptor and reduced the CBF in the rat oviduct . Despite recent findings from Jung et al which revealed that progesterone had the effect (from seconds to minutes) of rapidly increasing CBF as well as the long‐term effect (hours) of reducing CBF , a lower CBF in the Fallopian tube following long‐term effects of LNG was still regarded as one of the critical factors associated with tubal pregnancy, especially the one following LNG‐induced emergency contraceptive failure, as it took several hours for embryo transport through the Fallopian tubes.…”
Section: Discussionmentioning
confidence: 96%
“…The available literature reported that the percentage of ciliated cells decreased during pregnancy and with steroid contraception early in 1976 [30]. However, a previous study indicated that LNG-induced emergency contraception would only affect the Fallopian tubal physiology, including a reduction in the CBF, and not the tubal morphology [7]. LNG, as a second-generation synthetic progesterone, differs from progesterone in its structure and pharmacological properties, and has now been used as emergency contraception.…”
Section: Discussionmentioning
confidence: 99%